ROMANTISISME INGGRIS DAN AMERIKA: PERBANDINGAN FRANKENSTEIN DAN SCARLET LETTER - Syofyan, Donny (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2011)
Works of literature during Romantic period are totally unrelated to love, romance or attraction between men and women as widely understood. Rather they exert stress upon sense and feeling where individual freedom is highly esteemed. While Frankenstein (1818) reveals that power of mind and reasoning skill without feeling and conscience can lead to murder and death, Scarlett Letter (1850) shows that self-reliance and a strong spirit of individualism are part and parcel of one's belief. Key Words: romantisisme, simbolisme, kebebasan individu, Puritan,